Aerosol Codeposition of Ceramics: Mixtures of Bi2O3–TiO2 and Bi2O3–V2O5. Issue 3 (10th December 2014) - Exner, Jörg; Fuierer, Paul; Moos, Ralf
Abstract : Aerosol deposition (AD) is a promising method to apply ceramic films on a wide range of substrate materials. Until now, AD has mainly been performed using a single ceramic powder. In this work, mixtures of two different ceramic powders were prepared. The first mixture consisted of Bi2 O3 and TiO2 and the second consisted of Bi2 O3 and V2 O5, in stoichiometric ratios to form Bi4 Ti3 O12 and Bi4 V2 O11−δ, respectively. Aerosol codeposition produced films with homogeneously distributed particle fractions and thicknesses between 10 and 100 μm. Composite films were annealed to temperatures up to 750°C to enable an in situ calcination and attempted formation of the above‐mentioned compounds. Successful formation of Bi4 Ti3 O12 was tracked by hot‐stage X‐ray diffraction (XRD), and confirmed by dielectric measurements. Formation of the intended Bi4 V2 O11−δ, on the other hand, was not achieved, but rather BiVO4, which was confirmed by XRD, EDX and electrical measurements. The bismuth deficiency occurred during spray deposition, and is attributed to powder/material characteristics. Additional insight about the AD process is gained by comparing mixtures of oxides with different relative hardness values. Aerosol codeposition of ceramics may be an interesting new technique for producing porous functional ceramics.